2005
DOI: 10.1111/j.1600-0609.2005.00494.x
|View full text |Cite
|
Sign up to set email alerts
|

Platelet and granulocyte alloimmunisation in multitransfused Tunisian patients

Abstract: We determined the frequency of post-transfusion alloimmunisation against platelet and granulocyte antigens in 51 Tunisian polytransfused patients with haematological diseases. Serum samples were analysed by a standard and an antiglobulin-augmented lymphocytotoxicity technique, a granulocyte agglutination test, a granulocyte immunofluorescence test, a platelet immunofluorescence test and the monoclonal antibody-specific immobilisation of platelet antigens assay. No granulocyte-specific antibodies were detected.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
(24 reference statements)
0
4
0
Order By: Relevance
“…However, studies have mainly been performed in North American, European, and Oriental populations. In Tunisia, little is known about platelet immunogenetics and previous reports suggest that the frequency of platelet alloimmunization may differ with that seen in Whites and Asians (4–5). Tunisia is known to have a very heterogeneous population as a result of its history (6).…”
Section: Genotype and Gene Frequencies Determined In 116 Tunisian Blomentioning
confidence: 99%
“…However, studies have mainly been performed in North American, European, and Oriental populations. In Tunisia, little is known about platelet immunogenetics and previous reports suggest that the frequency of platelet alloimmunization may differ with that seen in Whites and Asians (4–5). Tunisia is known to have a very heterogeneous population as a result of its history (6).…”
Section: Genotype and Gene Frequencies Determined In 116 Tunisian Blomentioning
confidence: 99%
“…Little is known about the distribution of HPA systems and platelet antibody frequencies in Tunisians. Previous studies have identified the anti‐HPA‐5b antibody as the most prevalent in multi‐transfused patients and in patients with NAIT, whereas anti‐HPA‐1a antibody–which is frequent in Whites (Murphy & Williamson, 2000; Ahya et al , 2001; Kjeldsen‐Kragh et al , 2007) – has not been found in Tunisians (Skouri et al , 2003, 2005).…”
mentioning
confidence: 99%
“…Using leukodepleted blood will decrease alloimmunization rate against leukocytes but, because of their cost and sanctions in Iran, these types of human blood products are not always available. Several studies have reported that repeated transfusions led to the development of alloantibodies against the PLT or HLA antigens and different RBC blood group systems [14,16,17]. Despite the large number of nonleuko-depleted packed red cells and PLT concentrates transfused, 56.25% (135/240) of our multitransfused patients did not develop any allo-or auto-antibody, suggesting a degree of immune tolerance in these patients.…”
Section: Discussionmentioning
confidence: 55%
“…Despite the fact that alloantibodies are associated with transfusion risks, little is known about the extent and causes of these phenomena among patients with chronic hematologic diseases or the appropriate prevention methods [14]. There are no pertinent data on the number of multitransfused patients presenting platelet-or granulocytespecific antibodies especially in Iran.…”
Section: Introductionmentioning
confidence: 95%